2023
DOI: 10.1101/2023.08.01.551546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of an open KATPchannel reveals tandem PIP2binding sites mediating the Kir6.2 and SUR1 regulatory interface

Abstract: ATP-sensitive potassium (KATP) channels, composed of four pore-lining Kir6.2 subunits and four regulatory sulfonylurea receptor 1 (SUR1) subunits, control insulin secretion in pancreatic β-cells. KATPchannel opening is stimulated by PIP2and inhibited by ATP. Mutations that increase channel opening by PIP2reduce ATP inhibition and cause neonatal diabetes. Although considerable evidence has indicated PIP2in KATPchannel function, previously solved open-channel structures have lacked bound PIP2, and mechanisms by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…These include the structure of a human channel consisting of SUR1 and a mutant Kir6.2 harboring a pore mutation C166S known to stabilize channel opening as well as a G334D mutation that prevents ATP binding at the inhibition site (denoted by Kir6.2 C166S, G334D ), and the structure of a rodent SUR1-Kir6.2 fusion protein channel containing a Kir6.2 mutation H175K (Kir6.2 H175K ), which was incorporated to enhance PIP 2 binding. Recently, the cryoEM structure of a PIP 2 -bound open K ATP channel was reported in a preprint by Driggers et al [ 21 ]. Using a Kir6.2 variant harboring the neonatal diabetes-causing mutation Q52R (Kir6.2 Q52R ), which has been shown to increase channel open probability and decrease channel sensitivity to ATP inhibition in a SUR1-dependent manner [ 59 ], and by pre-incubating membranes expressing SUR1/Kir6.2 Q52R channels with natural long-chain PIP 2 , which provides more hydrophobic anchoring compared to synthetic short-chain PIP 2 , the authors observed, surprisingly, that not one but two adjacent well-resolved PIP 2 molecules occupy intramembrane positions between the Kir6.2 TMDs and SUR1-TMD0 ( Figure 3(a, b) ).…”
Section: Gating Regulation Of K Atp Channelsmentioning
confidence: 99%
See 4 more Smart Citations
“…These include the structure of a human channel consisting of SUR1 and a mutant Kir6.2 harboring a pore mutation C166S known to stabilize channel opening as well as a G334D mutation that prevents ATP binding at the inhibition site (denoted by Kir6.2 C166S, G334D ), and the structure of a rodent SUR1-Kir6.2 fusion protein channel containing a Kir6.2 mutation H175K (Kir6.2 H175K ), which was incorporated to enhance PIP 2 binding. Recently, the cryoEM structure of a PIP 2 -bound open K ATP channel was reported in a preprint by Driggers et al [ 21 ]. Using a Kir6.2 variant harboring the neonatal diabetes-causing mutation Q52R (Kir6.2 Q52R ), which has been shown to increase channel open probability and decrease channel sensitivity to ATP inhibition in a SUR1-dependent manner [ 59 ], and by pre-incubating membranes expressing SUR1/Kir6.2 Q52R channels with natural long-chain PIP 2 , which provides more hydrophobic anchoring compared to synthetic short-chain PIP 2 , the authors observed, surprisingly, that not one but two adjacent well-resolved PIP 2 molecules occupy intramembrane positions between the Kir6.2 TMDs and SUR1-TMD0 ( Figure 3(a, b) ).…”
Section: Gating Regulation Of K Atp Channelsmentioning
confidence: 99%
“…Panels (a) and (b) are taken from Figure 2 , and panel (c) from Figure 4 of bioRxiv preprint by Driggers et al. (reference [ 21 ]).…”
Section: Gating Regulation Of K Atp Channelsmentioning
confidence: 99%
See 3 more Smart Citations